2022
DOI: 10.1038/s41598-022-08110-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromitite layers indicate the existence of large, long-lived, and entirely molten magma chambers

Abstract: The classical paradigm of the ‘big magma tank’ chambers in which the melt differentiates, is replenished, and occasionally feeds the overlying volcanos has recently been challenged on various grounds. An alternative school of thought is that such large, long-lived and largely molten magma chambers are transient to non-existent in Earth’s history. Our study of stratiform chromitites in the Bushveld Complex—the largest magmatic body in the Earth’s continental crust—tells, however, a different story. Several chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 88 publications
2
50
0
Order By: Relevance
“…This allows plagioclase grains to nucleate heterogeneously at the bottom of the boundary layer with different orientations. Random orientations for heterogeneously nucleated crystals appear to be possible based on recent observations on chromitite layers 15 . Blue lines indicate the orientation of the a-axis of plagioclase grains along which growth is generally faster 65 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows plagioclase grains to nucleate heterogeneously at the bottom of the boundary layer with different orientations. Random orientations for heterogeneously nucleated crystals appear to be possible based on recent observations on chromitite layers 15 . Blue lines indicate the orientation of the a-axis of plagioclase grains along which growth is generally faster 65 .…”
Section: Methodsmentioning
confidence: 99%
“…1a). Grains may have random orientations (e.g., randomly oriented chromite grains nucleating heterogeneously on overturned contacts 15 ), unless large compositional gradients are present 14 . However, it is not uncommon for layered intrusions to have rocks that do not contain cotectic proportions of primocrysts 16 .…”
mentioning
confidence: 99%
“…However, Roeder and Reynolds (1991) found that chromite is, in fact, slightly more soluble at high pressure. Latypov et al (2017Latypov et al ( , 2022 proposed that a rapid transfer of a superheated magma from depth would lower pressure in the magma and could bring chromite only onto the liquidus which they modelled using the MELTS program. r An increase in fO 2 would ensure that most of the Cr is converted to Cr 3+ (the form of Cr in chromite) leading to chromite saturation (Ulmer 1969;Murck and Campbell 1986;Roeder and Reynolds 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The mass balance problem of chromitites (and stratiform PGE deposits) offers support to this concept of a large magma tank. [1] This is based on the weak assumption that individual layers of chromitite (in the RLS) are laterally continuous for 10–100 s of kilometres.…”
mentioning
confidence: 99%
“…There is, however, a growing body of evidence that suggests continental basaltic layered intrusions are formed by non-sequential sill emplacement into a resident mush (± transient melt lenses) [2] (Figure 1a). The RLS is also compartmentalised, [3,4] with compartments extending ≤ 50 km, and each being characterised by their own stratigraphic sequence of chromitites.…”
mentioning
confidence: 99%